Energy Conservation at Head Office Building of PT Petrokimia Gresik through Building Envelope Design - Edi Jamal Abdillah; wasiska iyati (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Badan Standardisasi Nasional (BSN) had regulated and recommended that buidings in Indonesia should maintain to conserve  energy. Head office building of PT Petrokimia Gresik located in such orientation which the longest side of the building always receives the annual sun radiation. the building envelope uses transparant material with 80% ratio of the surface and no shading device installed. This causes overheat  inside the building and more cooling devices are needed and affects to the energy consumption. Evaluative method in the form of observation and energy audit are applied to describe the real conditions and measure the energy consumption to obtain some inputs and recommendations. Experimental method is also applied to review the recommendations which may have effect to conserve energy.based on the audit, the IKE’s numbers are above the standard  while the dominant aspect for this case is cooling system. Through the envelope design approach with alternatives in the form of adjust the transparent material, adding shading devices, and double skin, obtained that combination between changing the transparent material and using double skin facade could decrease the energy consumption number reached 3,18%. With combination of tecnical recommendation in form of changing existing tools into low energy tools, the total yield could reach 41,1%. The IKE’s numbers could be decreased from 261 kWh/m2/year into 153,67 kWh/m2/year. Keywords: Energy Conservation, Office Building, Building Envelope